The Deep Mediatization of Student Loans: A Case Study of Digital-based Lending Practice in Indonesia - Noviani, Ratna; Jesica, Elok Santi (Jurnal Kawistara, 2024)
The emergence of digital technology has significantly transformed the lending landscape. One example of the rising influence of digital lending practice targeting university students in Indonesia is Cicil. This digital-based lending platform provides a Peer-to-Peer (P2P) lending service that aims to cater to higher education students who have been frequently excluded from various lending programs. This study explores the deep mediatization of loans within the ecosystem of digital platforms and how it transforms lending practices, as provided by Cicil. Utilizing the concept of deep mediatization by Andreas Hepp (2020) and a case study method, this study reveals that the logic of digital media has been adapted to and transformed lending practices. The practices of lending are becoming driven by datafication and connectivity between loan providers, users, and the digital platform ecosystem, leading to a spatially disembedded financial transaction and generating a sense of participatory and inclusivity in lending practices.